2015
DOI: 10.1111/mmi.12992
|View full text |Cite
|
Sign up to set email alerts
|

A new dehydratase conferring innate resistance to thiacetazone and intra‐amoebal survival of Mycobacterium smegmatis

Abstract: SummaryNontuberculous mycobacteria are innately resistant to most antibiotics, although the mechanisms responsible for their drug resistance remain poorly understood. They are particularly refractory to thiacetazone (TAC), a second-line antitubercular drug. Herein, we identified MSMEG_6754 as essential for the innate resistance of Mycobacterium smegmatis to TAC. Transposon-mediated and targeted disruption of MSMEG_6754 resulted in hypersusceptibility to TAC. Conversely, introduction of MSMEG_6754 into Mycobact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
16
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 57 publications
1
16
0
Order By: Relevance
“…Then, 50 absorbance units were collected by centrifugation and washed three times with PBS. The extraction of the cell envelope lipids was performed in three steps to harvest the apolar, polar, and mycolic acid lipid fractions as previously described (47,48). Both apolar and polar lipid fractions were analyzed with two-dimensional TLC for PDIM and the LOS lipid contents system A and system E, respectively, as earlier described by Besra (43).…”
Section: Methodsmentioning
confidence: 99%
“…Then, 50 absorbance units were collected by centrifugation and washed three times with PBS. The extraction of the cell envelope lipids was performed in three steps to harvest the apolar, polar, and mycolic acid lipid fractions as previously described (47,48). Both apolar and polar lipid fractions were analyzed with two-dimensional TLC for PDIM and the LOS lipid contents system A and system E, respectively, as earlier described by Besra (43).…”
Section: Methodsmentioning
confidence: 99%
“…We have previously shown that Mycobacterium smegmatis possesses a gene, MSMEG_6754, responsible for its remarkable resistance to TAC and involved in mycolic acid metabolism and that disruption of MSMEG_6754 in M. smegmatis was associated with impaired growth in Acanthamoeba castellanii (23). Interestingly, MSMEG_6754 encodes a putative dehydratase and is structurally related to the HadABC complex (23). Blast analyses revealed the presence of genes homologous to MSMEG_6754 in several NTMs, all of which possess intact hadABC genes (23).…”
Section: Significancementioning
confidence: 99%
“…Moreover, deletion of hadC in M. tuberculosis correlates with a loss of cording and attenuation of virulence in infected mice (22), thus emphasizing the intimate interplay between TAC resistance, mycolic acid biosynthesis, cording, and virulence. We have previously shown that Mycobacterium smegmatis possesses a gene, MSMEG_6754, responsible for its remarkable resistance to TAC and involved in mycolic acid metabolism and that disruption of MSMEG_6754 in M. smegmatis was associated with impaired growth in Acanthamoeba castellanii (23). Interestingly, MSMEG_6754 encodes a putative dehydratase and is structurally related to the HadABC complex (23).…”
Section: Significancementioning
confidence: 99%
See 1 more Smart Citation
“…Upon activation, TAC has recently been shown to bind to the HadA component of the HadABC dehydratase complex, leading to inhibition of mycolic acid biosynthesis (15). Interestingly, we and others have reported that NTM such as Mycobacterium avium (16), Mycobacterium smegmatis (17), and M. abscessus (18) are naturally resistant to TAC. However, a TAC analogue, SRI-224, was previously tested against M. avium and found to be more effective than TAC in vitro as well as in mice (16) and subsequently shown to be very active against M. tuberculosis (19).…”
mentioning
confidence: 99%